TIMELESS Promotes Tumor Progression by Enhancing Macrophages Recruitment in Ovarian Cancer - Xing, Xin; Gu, Fei; Hua, Lanyu; Cui, Xiaoxiao; Li, Dongxue; Wu, Zhiyong; Zhang, Rong (Frontiers in Oncology, 2021)
Objective Ovarian cancer (OV) is the most fatal and frequent type of gynecological malignancy worldwide. TIMELESS (TIM), as a circadian clock gene, has been found to be highly expressed and predictive of poor prognosis in various cancers. However, the function of TIM in OV is not known. This study was designed to investigate the biological functions and underlying mechanisms of TIM during OV progression. Methods Cell viability assay, cell migration assay, immunohistochemistry staining, qPCR analyses, and tumor xenograft model were used to identify the functions of TIM in OV. Bioinformatics analyses, including GEPIA, cBioPortal, GeneMANIA, and TIMER, were used to analyze the gene expression, genetic alteration, and immune cell infiltration of TIM in OV. Results TIM is highly expressed in OV patients. TIM knockdown inhibited OV cell proliferation, migration, and invasion both in vitro and in vivo. Genetic alteration of TIM was identified in patients with OV. TIM co-expression network indicates that TIM had a wide effect on the immune cell infiltration and activation in OV. Further analysis and experimental verification revealed that TIM was positively correlated with macrophages infiltration in OV. Conclusions Our study unveiled a novel function of highly expressed TIM associated with immune cell especially macrophages infiltration in OV. TIM may serve as a potential prognostic biomarker and immunotherapy target for OV patients.